Torque in nested Halbach cylinders - WEAIRE, DENIS LAWRENCE; COEY, JOHN MICHAEL DAVID (IEEE, 1999)
Permanent magnet variable flux sources are produced by rotating two nested N-segment, permanent magnet, Halbach cylinders. Torque is primarily an end effect, determined by field non-uniformities due to the fmite length and' segmented structure of the cylinders. Due to symmetry, one cylinder experiences zero torque In a uniform applied field. Experiment and numerical simulation reveal that the torque is composed of a dominant term of frequency 1/(2n) and harmonics at ( k N i l)/(Zn), where k is an integer.
PUBLISHED
Keywords: Permanent magnet variable flux souces, Halbach cylinders, torque, surface charge method, motors.